Snack Calorie Intake, Breakfast Frequency, and Nutritional Status in Adolescence - Zahra Anggita Pratiwi; Emy Huriyati; Toto Sudargo (Universitas Negeri Malang, 2023)
Poor eating habit is one of the causes of obesity in adolescents. A balanced diet is achieved every day, beginning with breakfast. Breakfast is often termed the most important meal of the day because it provides the food and energy we need for all upcoming activities. Snack consumption is thought to have an association with breakfast habits. People who do not tend to have breakfast replace it with snack consumption. This study has two main objectives: the first is to discover differences in adolescent characteristics, snack calorie intake, and total energy based on breakfast frequency, and the second is to discover differences in breakfast frequency based on adolescent nutritional status. It was a descriptive cross-sectional study in which proportionate stratified random sampling was used to select 140 adolescents. This study found that there was a significantly higher proportion of female adolescents who rarely had breakfast than male adolescents (p equal to 0.014; p less than 0.05). It showed that adolescents who rarely eat breakfast have a higher average energy snack than those who eat breakfast frequently. Obese adolescents were likely to eat breakfast, although this is not statistically significant. The researchers suggest a need for specific promotion for female adolescents regarding healthy breakfasts because this study found that female adolescents are more dominant in not having breakfast.